Benefit of oxytocin released by cervix stimulation in Mexican Holstein cattle - Morales, Ricardo; Criollo, Marco Antonio; Gonzalez, Mirvana; Medina, Gerardo; Manríquez, Olga Maritza; Gonzalez, Victor Manuel; Angulo, Carlos Villa (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The aim of this research is to investigate the relationship level of oxytocin released and the tactile stimulation of the cervix in Holstein cattle from the northwestern arid regions in México. Materials and Methods: The cervixes of 10 Holstein Friesian dairy cows in mid-lactation were manually stimulated for 60 sec. Oxytocin released in the blood was analyzed before and after stimulation. The enzyme-linked immunosorbent assay was used in the analysis to make oxytocin detectable by spectrometry techniques and by converting the luminescence absorbance of each sample into pg per mol. Results: The study revealed that tactile stimulation of the cervix increased oxytocin levels. The highest increase in oxytocin level was 10,940.8222 pg/mol, while the lowest increase in oxytocin level was 1,830.94254 pg/mol. Besides, the milk production by tactile stimulation of the cervix had a higher milk yield and a p-value of 9.4 × 10−4 (p < 0.05) in comparison to the monthly average without tactile stimulation. Conclusion: Tactile stimulation of the cervix activates the Ferguson reflex and increases the oxytocin released in the blood and increases the milk released from the alveolar glands. J. Adv. Vet. Anim. Res., 7(4): 608-613, Dec 2020 http://doi.org/10.5455/javar.2020.g458